Comparative analysis of eukaryotic microbial communities associated with Acropora formosa, sediment, and seawater in a coral reef ecosystem of Whale island, Nha Trang bay, Vietnam - Khanh Linh, Trinh; Van Ngoc, Bui (Vietnam Journal of Biotechnology, 2023)
In this study, eukaryotic microbial communities associated with coral Acropora formosa and its natural surroundings, sediment and seawater, in a coral reef ecosystem of Whale Island, Nha Trang Bay, Vietnam were investigated. First, genetic material was taken from Acropora formosa’s surface mucus layer (SML) as well as the sediment underneath and seawater above the colonies from four different sampling locations in a coral reef ecosystem. Subsequently, the data were sequenced using 18S rRNA gene amplicon sequencing method. Sequences (reads) were then analyzed in Rstudio version 4.2.0. Bioinfomatic tools such as DADA2 pipeline clustered the sequences into amplicon sequence variants (ASVs), to which the taxonomy was assigned using SILVA 132 database. The majority of the sequences was categorized at the kingdom and phylum levels, but fewer sequences were identified at genus and species level. The visualization of the results revealed changes in abundance and composition of the eukaryotic communities in all samples. The results demonstrated that phylum Dinoflagellata had the highest relative abundance in coral samples. Meanwhile, Ochrophyta was the most prevalent phylum in seawater samples. Notably, after filtering out the sequences with abundance less than 2%, only genus Symbiodinium appeared significantly in coral samples. The composition of samples from coral sampling sites was more consistent. The same was true for samples of seawater, whereas the composition of sediment samples varied more. Alpha and beta diversity indices confirmed that there were significant differences (p < 0.05) in abundance and composition of eukaryotic communities among three different habitats. These findings come as the first effort to explore the diversity of eukaryotic communities in different habitats and could be valuable for further study in functional profiling or metabolic functions of microbial communities in the coral ecosystem.